A brief account of the genesis of 4R nutrient stewardship. (14th July 2020) - Fixen, Paul E.
Abstract: In the last decade, awareness and use of the concept of 4R Nutrient Stewardship (4RNS) has increased dramatically among practitioners and researchers focused on nutrient management. The term "4R" refers to use of the right source, right rate, right time, and right place in nutrient management. These four factors have been recognized as the major pillars of nutrient best management practices for at least 30 yr. However, the framework of 4RNS (which embeds the 4Rs in a cropping system and landscape that supports the environmental, economic, and social dimensions of sustainability) is a recent development. The global framework evolved through multiple versions over the last decade in a multi‐sector collaborative effort to create a science‐based concept to guide all involved in nutrient management practice, research, and communication. However, evidence‐based 4RNS largely remains under development as measured datasets supporting simultaneous effects of sets of practices on performance indicators of sustainability are in short supply. Indicators include categories such as farmland productivity, soil health, nutrient use efficiency, water quality, air quality, greenhouse gas emissions, food and nutrition security, biodiversity, and economic value. Such collaborative, multidisciplinary research is underway and is intended to foster continued evolution of our understanding of what is "right" for specific sets of conditions. Progress has occurred in recognition of the shared goals of public and private sectors and the value of true collaboration in advancing science‐based nutrient stewardship.